Behavior change interventions delivered through interpersonal communication, agricultural activities, community mobilization, and mass media increase complementary feeding practices and reduce child stunting in Ethiopia - Kim, Sunny S.; Nguyen, Phuong Hong; Yohannes, Yisehac; Abebe, Yewelsew; Tharaney, Manisha; Drummond, Elizabeth; Frongillo, Edward A.; Ruel, Marie T.; Menon, Purnima (American Society for Nutrition, 2019)
Appropriate infant and young child feeding practices are critical for optimal child growth and development, but in Ethiopia, complementary feeding (CF) practices are very poor. Alive & Thrive (A&T) provided intensive behavior change interventions through 4 platforms: interpersonal communication (IPC), nutrition-sensitive agricultural activities (AG), community mobilization (CM), and mass media (MM). The aim of this study was to evaluate the impact of A&T intensive compared with nonintensive interventions (standard nutrition counseling and agricultural extension service and less intensive CM and MM) on CF practices and knowledge and child anthropometric outcomes.